2016
DOI: 10.1186/s12885-016-2457-0
|View full text |Cite
|
Sign up to set email alerts
|

Predictive factors for a long-term response duration in non-squamous cell lung cancer patients treated with pemetrexed

Abstract: BackgroundPemetrexed is widely used for the treatment of advanced non-squamous non-small-cell lung cancer (NSCLC). However, factors that can predict the benefits of pemetrexed therapy have not yet been defined.MethodsWe compared the clinical and molecule pathological characteristics of good and poor responders among a cohort of 1,848 non-squamous NSCLC patients who had received at least two cycles of pemetrexed therapy between November 2006 and February 2015. Among these cases, 92 good responders who were the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 31 publications
(31 reference statements)
0
20
0
Order By: Relevance
“…High tumor burden and brain metastasis are considered typical predictors of poor treatment outcome in lung cancer. In a Korean study, two or more metastatic sites and intra‐abdominal metastasis were poor prognostic factors for pemetrexed treatment . However, this study enrolled a majority of patients previously treated with other chemotherapeutic agents ( n = 270, 86.0%).…”
Section: Discussionmentioning
confidence: 99%
“…High tumor burden and brain metastasis are considered typical predictors of poor treatment outcome in lung cancer. In a Korean study, two or more metastatic sites and intra‐abdominal metastasis were poor prognostic factors for pemetrexed treatment . However, this study enrolled a majority of patients previously treated with other chemotherapeutic agents ( n = 270, 86.0%).…”
Section: Discussionmentioning
confidence: 99%
“…According to Lee et al, NSCLC patients with an EML4-ALK rearrangement showed significantly higher response rates to PEM and improved progression-free survival than control patients [9]. Several studies have also shown that PEM treatment in NSCLC with an EML4-ALK rearrangement is superior in response rate and survival than without this rearrangement [10][11][12][13]. These results suggest that an alteration in the intracellular signaling pathway involved in EML4-ALK has a synergistic effect on the cytotoxic effect of PEM; however, the detailed mechanism has yet to be elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…Jiang et al 26 reported significant better overall response rate and median PFS in the EGFR -mutated lung adenocarcinoma patients receiving first-line pemetrexed/platinum combinations compared to those without EGFR mutation. In contrast, Park et al 17 recently demonstrated the significant association of the EGFR mutation with poor PFS in nonsquamous NSCLC patients treated with first-line pemetrexed-containing chemotherapy. In our study, the median OS for pemetrexed maintenance was 22.3 months which is much longer than those of previous trials.…”
Section: Discussionmentioning
confidence: 89%
“…Third, the ALK translocation test was performed only in a portion of the population, thus the possible influence of this driving rearrangement on the clinical outcome could not be excluded. Although conflicting data exist, several studies have suggested that ALK rearrangement may be associated with better clinical outcome for those treated with pemetrexed-based chemotherapy than wild-type for ALK 17 30 . Fourth, treatment-related quality of life and side effects according to different treatment strategy were not investigated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation